Impact Analysis of Sister Province Cooperation Between the Government of South Sulawesi Province (Indonesia) and Ehime Prefecture (Japan) - Hidayat, Muh. Taufik; Suhafid, Muh. Zulhamdi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the impact of cooperation between the South Sulawesi government and Ehime Prefecture within the Sister Province framework. The approach used in this article is paradiplomacy and sister province. By using qualitative research methods with a literature study approach. The results showed that since the signing of the MoU, sister province cooperation between the South Sulawesi government and Ehime Prefecture has not been effective and massive in its application. The application carried out is by sending 10 people from South Sulawesi to Ehime Japan to conduct training in tuna fish technology management. In addition, in 2021, the Ehime government provided grant assistance to the South Sulawesi government in the form of ambulances and fire fighting vehicles. However, behind the positives, the cooperation between the two provinces experienced several obstacles, namely first, the replacement of Mr. Nurdin Abdullah as Governor of South Sulawesi which caused communication and interaction to not run smoothly. Second, there was overlapping coordination between South Sulawesi government institutions. Third, facing the Covid 19 pandemic, so that mobility activities are not going well.